Coping with catastrophe: the value of endoscopic vascular injury training. Issue 3 (29th December 2014) - Padhye, Vikram; Valentine, Rowan; Sacks, Raymond; Ooi, Eng H.; Teo, Charlie; Tewfik, Marc; Wang, Dehui; Wormald, Peter‐John
<x xml:space="preserve">Abstract</x> Background Inadvertent injury to the internal carotid artery (ICA), if poorly managed, not only presents a risk of exsanguination but can also result in significant long‐term morbidity. Through the implementation of a novel animal model of endoscopic carotid artery injury (CAI), effective techniques to manage this scenario have been developed. The Vascular Injuries Workshop has trained over 110 surgeons in these techniques. This study reviews events of major arterial hemorrhage managed by surgeons who completed this vascular injury workshop training. Methods We report a retrospective multicenter case series of patients who required endoscopic management of intranasal major arterial hemorrhage. Delegates who had attended the course were contacted by e‐mail and surveyed with regard to instances of major arterial bleeding and the management undertaken. Patient demographics, tumor type, factors influencing injury, management technique, and outcomes were reviewed. Results The cases reported herein are characterized as follows: 9 cases are reported in total, 3 male, 6 female; age range 37 to 82 years; 1 basilar artery, and 8 ICA injuries. Each case was successfully managed endoscopically with intraoperative muscle patch application. There were no deaths, 1 case of pseudoaneurysm with successful endovascular treatment, 2 cases of impaired carotid flow, and 1 carotid dissection was conservatively managed. There were no permanent neurological sequelae or other permanent morbidity. Conclusion The Vascular Injuries Workshop arms surgeons with a structured approach to managing the surgical field and provides effective hemostatic techniques in the face of impending catastrophe. In comparison to the existing literature on ICA rupture, our results show trained surgeons are well equipped to achieve safe outcomes for their patients.